Effect dual inoculation of Azotobacter and Azospirrilum on the productive trait upland red rice cultivar. Issue 1 (October 2020) - Muhidin,; Syam'un, E; Kaimuddin,; Musa, Y; Sadimantara, G R; Leomo, S; Sutariati, G A K; Yusuf, D N; Rakian, TC
Abstract: The aims of this research were to analyze the effect of dual inoculation of Azotobacter and Azospirrilum on the productive trait upland red rice cultivar. The research was conducted in the field of experimental farm, department of agronomy, the faculty of agriculture, Halu Oleo University. This research arranged in split-plot design with dual inoculation treatment in the main plot and cultivar differences in the subplot, with three replications. The dual inoculation treatment consist of three levels as follows: b0 = without inoculation, b1 = treatment with Azotobacter 2.5 L ha −1 + Azospirillum 2.5 L ha −1 and b2 = Treatment with Azotobacter 5.0 L ha −1 + Azospirillum 5.0 L ha −1 . The type of cultivar used were (v1 ) = Labandiri, (v2 ) = Jangkobembe, (v3 ) = Ranggohitam and (v4 ) = Paedara. The result showed that the bacterial fixator application would (1) increase the productive tillers, and (2) increase rice productivity through the increase of productive tillers and grain weight.